Participant satisfaction with dementia prevention research: Results from Home‐Based Assessment trial. Issue 11 (5th October 2018) - Sano, Mary; Egelko, Susan; Zhu, Carolyn W.; Li, Clara; Donohue, Michael C.; Ferris, Steven; Kaye, Jeffrey; Mundt, James C.; Sun, Chung‐Kai; Aisen, Paul S.; Feldman, Howard H.
Abstract: Introduction: Little is known about factors affecting motivation and satisfaction of participants in dementia prevention trials. Methods: A Research Satisfaction Survey was administered to 422 nondemented older adults who participated in the Home‐Based Assessment trial. Results: Overall satisfaction was high, with means of all individual items near to above a value of 3 on a scale from 1 (worst) to 4 (best). Greater satisfaction was associated with staff‐administered interviews versus automated technologies. The most liked aspects of research participation were volunteerism, opportunity to challenge and improve mental function, and positive interactions with staff. The least liked aspect was repetitiveness of the assessments. Participants requested more contact with staff and other older adults and more feedback on performance. Discussion: Older adults' participation in research was primarily motivated by altruism. Methodologies that facilitate human contact, encourage feedback and novelty of tasks should be incorporated into future trial design.